Combined reverse engineering and CAD approach for mould modelling in casting simulation. (August 2014) - Salmi, A.; Atzeni, E.; Calignano, F.; Minetola, P.; Iuliano, L.
<x content-type="archive" xml:space="preserve">Abstract</x> Casting process simulation is nowadays established as a strategic tool in process optimisation to improve product quality. However, sometimes the required three-dimensional mathematical model of the casting is not available, because the original drawings are not-up-to date and parts are subjected to design changes. In these cases, reverse engineering (RE) is the most suitable method to reconstruct the geometrical model of the casting. In this paper, a RE-based procedure is proposed to obtain the three-dimensional CAD model of a casting from its physical equipment. The proposed procedure involves four phases: pre-digitising, digitising of equipment parts, surface reconstruction, and three-dimensional CAD modelling. An aeronautical part fabricated by sand casting is selected as case study to verify the feasibility of this approach. Outcomes prove that the RE methodology is adequate to virtually reconstruct the geometry of each single part of the equipment as well as the whole geometry of the assembled mould.